2013
DOI: 10.1590/s2317-15372013000400013
|View full text |Cite
|
Sign up to set email alerts
|

Initial development of red and cultivated rice in response to light and air temperature

Abstract: Light is an important factor in the cold protection process in plants. The objective of this study was to evaluate the relationship between temperatures and levels of quantity and quality of light on the initial development of rice cultivars and red rice biotypes. Two experiments were conducted, in the laboratory and in the greenhouse, from July to November 2012. The factors studied in experiment I were: temperatures (25 ºC and 18/13 ºC); cultivars/biotypes (IRGA 424 and PUITÁ INTA-CL/AV 6716 and AV 6722) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Venske et al (2013) observaram, tanto para cultivares de arroz irrigado quanto para biótipos de arroz-vermelho, maiores valores de comprimento de radícula no escuro quando comparadas aos regimes de luz, sendo esse comportamento mais notável em baixas temperaturas (18/13 o C). Esses autores destacam que plântulas com esse comportamento têm seu desenvolvimento afetado em condições de frio e ausência de luz, pelo fato de priorizarem o investimento das reservas da semente para o crescimento da raiz, podendo haver falta de reservas para o crescimento da parte aérea.…”
Section: Resultsunclassified
“…Venske et al (2013) observaram, tanto para cultivares de arroz irrigado quanto para biótipos de arroz-vermelho, maiores valores de comprimento de radícula no escuro quando comparadas aos regimes de luz, sendo esse comportamento mais notável em baixas temperaturas (18/13 o C). Esses autores destacam que plântulas com esse comportamento têm seu desenvolvimento afetado em condições de frio e ausência de luz, pelo fato de priorizarem o investimento das reservas da semente para o crescimento da raiz, podendo haver falta de reservas para o crescimento da parte aérea.…”
Section: Resultsunclassified
“…We used red rice (Oryza sativa L.) as the model plant species in our experiment, owing to its large dependence on water availability (Leopold et al 2006). During vegetative stages of development, stress caused by drought decreases the plant height and its leaf area, while lack of water during the flowering stage reduces the grain yield (Venske et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This results in water or nutrient depletion in the competitor (Rizzardi et al, 2001). Venske et al (2013) assessed the initial development of cultivated and weedy rice seedlings and found that the latter exhibits morphological variables superior to those of its cultivated counterpart, increasing in low light conditions. This study corroborates the results observed for the morphological variables of the root system, such as the greater length, perimeter, and area of the weed species.…”
Section: Resultsmentioning
confidence: 99%
“…Inefficient weed control is one of the major limiting factors of the productive potential of irrigated rice (Venske et al, 2013). In this respect, weedy rice (Oryza sativa L.), also known as red rice, is one of the main weed species (Shivrain et al, 2010).…”
Section: Introductionmentioning
confidence: 99%